Frontiers in health policy research. Volume 6 - Cutler, David M.; Garber, Alan M.; National Bureau of Economic Research (Cambridge, Mass. ; London : MIT, 2003)
This important series presents timely economic research on health care and health policy issues. Each volume contains papers from an annual conference of researchers, government officials, and policy experts held in Washington, D.C. Topics include the effects of health policy reforms, changes in health care organization and management, measurement of health outcomes, health care output and productivity, the role of health-related behavior, health and aging, health and children, and health care financing.
On cover: National Bureau of Economic Research.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Medical policy; Health Policy; Politique sanitaire; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Public Health; MEDICAL -- Health Policy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Diseases; MEDICAL -- Health Care Delivery; Medical policy; ECONOMICS/Health Economics; SOCIAL SCIENCES/Political Science/Public Policy & Law